Studies on Preparation and Preservation of Squash from Wild Pomegranate (Punica granatum L.) Fruits and its Quality Evaluation During Storage - Thakur, N. S.; Dhaygude, G. S.; Thakur, Abhimanyu; Kumar, Pradeep; Hamid (International Journal of Bio-resource and Stress Management, 2018)
Wild pomegranate fruit is a rich source of organic acids apart from having appreciable amount of sugars, anthocyanins, phenols, ascorbic acid and minerals like phosphorus, calcium, potassium, iron etc. The present studies were undertaken for the development of squash from wild pomegranate fruit and its quality evaluation during storage of six months. Different combinations of juice and sugar syrup/TSS (Total soluble solids) were tried to standardize proper combination for squash. The squash prepared by following the best selected recipe (42% juice and 45 oB TSS) was packed in glass and PET (Polyethylene terephthalate) bottles and stored for six months under ambient and refrigerated temperature conditions. Squash could be safely stored for a period of six months under both the storage conditions without much change in various quality characteristics. Various physico-chemical characteristics increased/decreased like TSS (45 to 45.68 oB), reducing sugars (22.66 to 31.50%), titratable acidity (1.51 to 1.40%), ascorbic acid (6.74 to 3.26 mg 100 ml-1), total phenols (48.34 to 38.89 mg 100 ml-1) and anthocyanins (9.15 to 3.58 mg 100 ml-1). Various sensory characteristics scores of squash like colour (8.00 to 6.37), body (8.10 to 6.97), taste (8.10 to 6.97), aroma (8.20 to 6.57) and overall acceptability (8.05 to 6.39) decreased during storage. However, the changes in the quality characteristics of the squash were slower in refrigerated storage conditions as compared to ambient conditions. Both the packaging materials viz. PET and glass bottles were found suitable, with comparatively less changes occurring in glass bottles stored under refrigerated conditions.